Using local scientific knowledge for transboundary conservation: distribution modelling for the taruka in South America - Nicolás Fuentes-Allende; Cristina Mata; Javier Barrio; Paulo Corti; Gabriel Llerena; Velia Mendoza; Ángela Nuñez; Ramiro Ovejero; Luis F. Pacheco; Hernán Pastore; Josef Rechberger; Hector A. Regidor; et al. (Oryx)
Effective conservation management of threatened species with transboundary distributions is a challenge, requiring international coordination to ensure that country-specific actions align with regional imperatives. Many international conservation efforts overlook species needing attention and fail to incorporate the field expertise of local researchers in regional-level assessments. Here we focus on the taruka Hippocamelus antisensis, a threatened and little-studied deer of the Central Andes Ecoregion in South America. Since 2016, experts, managers and governmental authorities from all countries encompassing the species’ range have gathered to collate information about its presence and coordinate efforts to conserve it. We constructed taruka distribution models using historical records and more recent sightings reported during the last 50 years. Our findings revealed several critical insights: slope, normalized difference vegetation index (NDVI) during the dry season, and daily and seasonal temperature variability are primary predictors of taruka distribution, and the largest part of its range is in Peru (54%), followed by Bolivia (30%), Argentina (10%) and Chile (6%). The species’ core distribution is confined to the western and eastern limits of the Central Andes Ecoregion, bordered by the Sechura and Atacama Desert to the west and the Yungas Forest to the east. Protection is limited, with only 12 and 8% of the core and non-core areas, respectively, of the species’ range under formal protection. We recommend safeguarding connectivity of the core distribution by establishing transboundary protected areas, improving taruka coexistence with local communities, strengthening and formalizing international collaboration amongst taruka experts and raising the species’ appeal amongst policymakers and the public. In particular, we hope to encourage international collaboration between Southern Hemisphere specialists. This is important because these researchers have extensive field knowledge that could improve global conservation efforts, especially in regions that lack adequate conservation funding.